Hermeneutika al-Qur’an dalam Perspektif Studi Islam Kontemporer: Antara Tradisi dan Pembaruan - Ahmad Fauzi Hakim; Siti Nurhaliza Putri; Muhammad Rizal Anshari (Al-Jinan : Jurnal Studi Islam, 2026)
Qur’anic hermeneutics has undergone significant development in contemporary Islamic studies, marked by the emergence of new approaches bridging classical exegetical traditions and modern demands. This study aims to analyze the dynamics of Qur’anic hermeneutics in contemporary Islamic studies, examining tensions between traditionalist and reformist approaches. A qualitative library research method with hermeneutic analysis and comparative study of major thinkers was employed. Results show that contemporary Qur’anic hermeneutics evolves through three main currents: traditionalist, modernist, and contextualist, each possessing distinct epistemology and methodology. The study concludes that an integrative approach is needed that honors traditional heritage while critically and constructively responding to contemporary challenges.